Pelagic amphipods (Crustacea: Amphipoda: Hyperiidea) in western Mexico. 6. Superfamily Vibilioidea. Families Paraphronimidae and Vibiliidae - Gasca, Rebeca; Hendrickx, Michel E. (Zootaxa, 2021)
Ten species belonging to the families Paraphronimidae and Vibiliidae were collected during a deep-water survey off western Mexico: two species of Paraphronima and eight species of Vibilia. This represents about 40% of all known species of these two genera world-wide. A total of 419 males and 607 females were obtained in 39 samples from localities in the Gulf of California (33) and off southwestern Mexico (6). Vibilia armata was by far the most frequently (32 localities) and most abundantly (687 specimens, 67% of the total) collected species, followed by V. longicarpus (231 specimens in nine localities) and P. crassipes (35 specimens in 9 localities). Co-ocurrence of species of Vibilioidea in our samples was very low, with maxima of seven and five species collected in the same sample, once each. Considering previous records, a total of 16 species of Vibilioidea (almost 70% of all known species) have now been reported from western Mexico: two species of Paraphronima and 14 species of Vibilia, including V. australis occasionally reported in the area as its junior synonym, V. wolterecki.